(untitled) (Revista Inclusiones, 2020)
The aim of this work is the consideration of effective ways of implementation and substantiation of personalized approach for physical activities and sports among the students of different age. The presented paper demonstrates that physical training and sport loads in student environment define the opportunity of not only successful educational or scientific progress, but also of a positive social integration. The authors see the sport’s social meaning in higher education institution as a function of carrying out an applied activity with correlation into the successful professional medium. The relevance of the paper is due to the general acknowledgement that physical culture and sports in educational institution is perceived as not only a part of academic load by the subjects of general professional cycle, but also as a mean of students’ socialization.